Framing Analysis of Sumatera Flood Disaster News in Kompas.com and Detik.com Media December 2025 Edition - Mhd Aziz Syahridani; Winda Kustiawan (Yayasan Darussalam Bengkulu, 2026)
The flash floods that struck Aceh, North Sumatra, and West Sumatra in November–December 2025 resulted in more than 1,200 fatalities and massive infrastructure damage. Media coverage of this disaster has the potential to shape public perception in an unbalanced way if it is not presented comprehensively. This study aims to analyze and compare the framing of news coverage of the Sumatra floods on the online media outlets Kompas.com and Detik.com to reveal differences in the construction of reality and trends in information presentation in both media outlets. The approach used is descriptive qualitative analysis based on Robert N. Entman’s framing model, which encompasses four elements: problem definition, identification of causes, moral judgment, and recommended solutions. The results of the study show that Kompas.com frames the floods as an ecological structural failure resulting from massive deforestation, weaknesses in permit management, and a capitalist development orientation, with long-term solutions involving ecosystem restoration and a moratorium on extractive activities. In contrast, Detik.com framed the disaster as a humanitarian emergency, focusing on the physical impacts, the need for a rapid response, and administrative measures such as declaring a national disaster and river normalization. These differences in framing reflect the editorial tendencies of each media outlet, which influence how the public understands the root causes of the problem and the priorities for disaster management.